High-Temperature Internal Friction Of Alpha Brass - C. Zener; D. Van Winkle; H. Nielsen (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1942)
THE internal friction of metals has been studied frequently at elevated temperatures.1-4 In most cases it rises rapidly with increasing temperature. The notable exceptions are ferromagnetic materials, and lead.2 This paper describes an investigation of the general features of the high-temperature internal friction of 70-30 alpha brass. EXPERIMENTAL METHOD The internal friction of a metal is a measure of the rate at which it dissipates energy of vibration. The measure adopted here, I/Q, is (I/2p) times the specific damping capacity, a measure commonly used by engineers. In the measurements of this investigation, the stress level was kept so low that the observations were independent of the stress. The general method of making such measurements, and of observing the temperature of the specimen during a measurement, has been described elsewhere.5,6 The driver and detector coils were wound with wire insulated with glass thread, in order to withstand the high temperatures used. In previous work electrical eddy currents in the specimen served as the coupling between the mechanical vibration of the specimen and the electrical circuits of the driver and detector. The high values of the internal friction in the present investigation rendered this coupling insufficient. In order to increase this coupling, pole pieces cut from ordinary telephone diaphragms were attached to the specimen. A mixture of French chalk and water glass proved a satisfactory cement. All measurements were made at the fundamental frequency for transverse vibration, which lay between 600 and 900 cycles per second. SPECIMENS The measurements described herein were made upon a single cylindrical rod of brass, kindly furnished by Dr. Cyril Stanley Smith, of the American Brass Co. This rod was the specimen E of the set of alphabrass rods described in an earlier paper.6 Successively larger grain sizes were obtained by annealing at successively higher temperatures. A slice was cut off one end after each set of measurements. Grain counts were made on each slice by W. E. Lindlief, of the American Brass Co. Nine fields were viewed on each piece, located as shown in Fig. I. Results are given in Table I. The grain size is defined in the usual way; namely, Grain size = I/n ½ where n is the mean number of grains per square millimeter. EXPERIMENTAL RESULTS This paper is concerned exclusively with the part of the internal friction that becomes dominant at high temperatures. It is thus desirable to separate this part of the internal friction from the part that is